Identification of ORC1/CDC6-Interacting Factors in Trypanosoma brucei Reveals Critical Features of Origin Recognition Complex Architecture - Tiengwe,C; Marcello,L; Farr,H; Gadelha,C; Burchmore,R; Barry,JD; Bell,SD; McCulloch,R (PLoS ONE, 2012)
DNA Replication initiates by formation of a pre-replication complex on sequences termed origins. In eukaryotes, the pre-replication complex is composed of the Origin Recognition Complex (ORC), Cdc6 and the MCM replicative helicase inconjunction with Cdt1. Eukaryotic ORC is considered to be composed of six subunits, named Orc1–6, and monomeric Cdc6is closely related in sequence to Orc1. However, ORC has been little explored in protists, and only a single ORC protein,related to both Orc1 and Cdc6, has been shown to act in DNA replication inTrypanosoma brucei. Here we identify threehighly diverged putativeT. bruceiORC components that interact with ORC1/CDC6 and contribute to cell division. Two ofthese factors are so diverged that we cannot determine if they are eukaryotic ORC subunit orthologues, or are parasite-specific replication factors. The other we show to be a highly diverged Orc4 orthologue, demonstrating that this is one ofthe most widely conserved ORC subunits in protists and revealing it to be a key element of eukaryotic ORC architecture.Additionally, we have examined interactions amongst theT. bruceiMCM subunits and show that this has the conventionaleukaryotic heterohexameric structure, suggesting that divergence in theT. bruceireplication machinery is limited to theearliest steps in origin licensing.